Improved Electrochemical Performance Based on Nanostructured SnS2@CoS2–rGO Composite Anode for Sodium-Ion Batteries - Wang, Xia; Li, Xueying; Li, Qiang; Li, Hongsen; Xu, Jie; Wang, Hong; Zhao, Guoxia; Lu, Lisha; Lin, Xiaoyu; Li, Hongliang; Li, Shandong (Nano-Micro Letters, 2018)
A promising anode material composed of SnS2@CoS2 flower-like spheres assembled from SnS2 nanosheets and CoS2 nanoparticles accompanied by reduced graphene oxide (rGO) was fabricated by a facile hydrothermal pathway. The presence of rGO and the combined merits of SnS2 and CoS2 endow the SnS2@CoS2–rGO composite with high conductivity pathways and channels for electrons and with excellent properties as an anode material for sodium-ion batteries (SIBs). A high capacity of 514.0 mAh g−1 at a current density of 200 mA g−1 after 100 cycles and a good rate capability can be delivered. The defined structure and good sodium-storage performance of the SnS2@CoS2–rGO composite demonstrate its promising application in high-performance SIBs. Highlights: 1 A flower-like nanostructured composition of SnS2@CoS2 spheres associated with reduced graphene oxide (rGO) was prepared by a facile method. 2 The anode based on SnS2@CoS2–rGO composite exhibited excellent cycling stability and rate capability for sodium-ion batteries (SIBs).